Correlative outcomes of maternal immunization against RSV in cotton rats - Jorge C. G. Blanco; Lori M. Cullen; Arash Kamali; Fatoumata Y. D. Sylla; Zenab Chinmoun; Marina S. Boukhvalova; Trudy G. Morrison (Taylor & Francis Group, 2022)
Maternal anti-respiratory syncytial virus (RSV) antibodies protect neonates from RSV disease throughout first weeks of life. Previous studies of maternal immunization in cotton rats showed that a single immunization during pregnancy of RSV-primed dams with virus-like particles (VLPs) assembled with pre-fusion F protein and the wild type G protein boosted their RSV serum antibody concentration and protected pups early in life against RSV challenge. We extended these findings by evaluating responses to RSV infection in litters from two consecutive pregnancies of immunized dams. Using an RSV-primed population of VLP-vaccinated and unvaccinated dams, we defined correlations between dams' and litters' RSV neutralizing antibodies (NA); between litters' NA and protection; and between litter's NA and their lung expression of selected cytokines, of a first or of a second pregnancy. Lung pathology was also evaluated. We found positive correlation between the NA titers in the dams at delivery and the NA in their first and second litters and negative correlations between the litters' NA and protection from RSV challenge. Vaccination of dams modulated the mRNA expression for IFNγ and IL-6 and lung pathology in the first and in the second litter at different times after birth, even in the absence of detectable NA. Maternal RSV vaccination enhanced the levels of antibodies transferred to offspring and their protection from challenge. Importantly, maternal vaccination also impacted the immunological and inflammatory response of the offspring's lungs well into maturity, and after the antiviral effect of maternally transferred NA waned or was no longer detectable.